Ambientes familiares y la adaptación afectiva en los niños con discapacidades de la Escuela de Educación Especial Azucena Chang de Orellana - Albiño Estrada, Cinthya Marianela (2019)
In Ecuador, educational authorities have established guidelines to facilitate the affective adaptation of children with disabilities in the education system, detecting various reasons why, for a student according to his degree of disability, it is more difficult for him to access learning than for his students. companions. On the other hand, the exclusion or segregation of children who have some type of disability, is a problem that transcends in many schools and educational units where this type of practice is still suffered. Disability is only one of the factors of exclusion, hence the importance of approaching the issue from a conscientizing perspective. Many parents who have children with disabilities have the question of educating their children in regular schools or special schools, where the fact that children with some type of disability attend regular school does not necessarily ensure that they are participating in equal conditions. in school activities. In this paper we will describe the incidence of family environments in the affective adaptation in children with disabilities of the School of Special Education "Azucena Chang de Orellana", due to the lack of knowledge the family can run a series of risks when facing the relationship with the person with a disability: that one father be more responsible than the other, that other siblings feel unattended, that siblings become pseudo-parents, that the family be closed to the social relationship, etc., making it necessary to propose alternative solutions that reduce the risks of this problem.